TELAAH KRITIS âCOUNTER LEGAL DRAFT KOMPILASI HUKUM ISLAMâ (Reorientasi Fikih Hukum Keluarga Islam Indonesia) - khair, abul (Pasca Sarjana STAIN Watampone, 2016)
The movement of Islamism and modernization in the field of Family Law in Indonesia did not stop after the regulated on the Compilation of Islamic Law (KHI).